Collective Bargaining Rights, Policing, and Civilian Deaths - Jamein Cunningham; Donna Feir; Rob Gillezeau (Institute of Labor Economics (IZA), 2021)
Do collective bargaining rights for law enforcement result in more civilian deaths at the hands of the police? Using an event-study design, we find that the introduction of duty to bargain requirements with police unions has led to a significant increase in non-white civilian deaths at the hands of police during the late twentieth century. We find no impact on various crime rate measures and suggestive evidence of a decline in police employment, consistent with increasing compensation. Our results indicate that the adoption of collective bargaining rights for law enforcement can explain approximately 10 percent of the total non-white civilian deaths at the hands of law enforcement between 1959 and 1988. This effect is robust to a contiguous county approach, accounting for heterogeneity in treatment timing, and numerous other specifications. While the relationship between police unions and violence against civilians is not clear ex-ante, our results show that the popular notion that police unions exacerbate police violence is empirically grounded.
Keywords: J15; K42; J45; J58; N3; 330; police unions; policing; deaths by legal intervention; collective bargaining; discrimination